Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp. NCIM 5124). Issue 3 (March 2015) - Rohamare, Sonali; Gaikwad, Sushama; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit
Highlights Serine protease from Nocardiopsis sp. cloned and expressed. pET-39b (+) served as better vector than pET-22b (+). Homology model suggested the protein to be a member of PA clan. Unfolding cooperativity was studied by novel computational approach. Docking with substrate showed important binding interactions.